Biological and molecular characterization of a Baculovirus isolated from legume pod borer, Helicoverpa armigera (Hubner) (Noctuidae: lepidoptera) - Sridhar-Kumar, C.; Kumar, P. Lava; Sireesha, K.; Ranga Rao, V.; Waliyar, Farid; Rambabu, C. (2008)
Helicoverpa armigera (Hubner) (Noctuidae: Lepidoptera), commonly known as legume pod borer, is a major insect pest of legume crops in the semi-arid tropics. A baculovirus of type nucleopolyhedrovirus (NPV) was isolated from this insect during natural epizootics at ICRISAT. Patancheru (Andhra Pradesh, India). Electron microscopic studies showed that the occlusion bodies (OBs) are in polyhedral shape and approximately 2 pin in diameter containing multiple nucelocapsids per envelope and purified virus particles revealed bacilliform tocylindrical shaped structures of size of 282 x 49 nm. In bioassays the virus on 2nd and 3'* instar H. arinligera larvae had LCs0 values on 71h day are 2.30 x lo4 and 1.5 x lo5 POBs/ml and LTsO values at virus con cent ratio^^ of 1.8 x 10' POBsIml are 118.80 and 133.92 hr respectively. The virus yield was high in the fieldcollected larvae (5.60 x lo9 POBs/larva and/or 14.01 x loy POBs/ml) than laboratory reared larvae (5.02 x109 POBs /larva and/or 12.42~lo 9P OBS/~Ib)u,t no variation in their virulence (LCs0 values on 7t'1 day: 1.79 x 105 and 1.11 x lo5 POBs/ml). Using a degenerate oligonucleotide primer set polyhedrin gene of the virus was amplified by PCR. This resulted in a 744 bp product w hich was cloned and sequenced. The nucleotide gene sequence had a high ho~nology with several NPVs, specifically with NPV from Mutnestra brassicue (97%), Marnestra cor$gl~rura (97%) and Leucariirl seperata (95%) (Noctuidae: Lepidoptera) and these three viruses shared a unique restriction site for Xlzo-I enzyme at nucleotide position 130 (M. brossicae and M. cor?fi,purata) and at 670 (L. seperata). The phylogenetic analysis showed that the virus belongs to Group-I1 NPVs and the virus was named as Helicoverpa arniigera N~~cleopolyhedorivrus (NPV), Patancheru strain. This is the 81h report worldwide and first report from the Indian subcontinent to be described the complete polyhedrin gene of a NPV isolated from H. armigera. Field efficacy studies of this virus (250 LE/ha) againstH. arrnigem on chickpeacrop wascomparable with fields sprayed with n synthetic insecticide (endosulfan at 0.07%) confirming its i~sefi~lnefsosr controlling legume pod borer.